Interference of Gold Nanoparticles with In vitro Endotoxin Detection Assays - Vetten, Melissa A.; Gulumian, Mary (Current Nanoscience, 2020)
Background: Endotoxin-free engineered nanoparticle suspensions are imperative for their successful applications in the field of nanomedicine as well as in the investigations in their toxicity. Gold nanoparticles are known to interfere with various in vitro assays due to their optical properties and potential for surface reactivity. In vitro endotoxin testing assays are known to be susceptible to interference caused by the sample being tested. Objective: This study aimed to identify a preferred assay for the testing of endotoxin contamination in gold nanoparticle suspensions. Methods: The interference by gold nanoparticles on three assays namely, the commonly used limulus amebocyte lysate chromogenic assay, the limulus amebocyte lysate gel-clot method, and the less common recombinant Factor C (rFC) assay, was tested. Results: Possible interference could be observed with all three assays. The interference with the absorbance- based chromogenic assay could not be overcome by dilution; whilst the qualitative nature of the gel-clot assay excluded the possibility of distinguishing between a false positive result due to enhancement of the sensitivity of the assay, and genuine endotoxin contamination. However, interference with the rFC assay was easily overcome through dilution. Conclusion: The rFC assay is recommended as an option for endotoxin contamination detection in gold nanoparticle suspensions.
Keywords: Endotoxins